Prognostic and clinicopathological significance of Beclin-1 in non-small-cell lung cancer: a meta-analysis - Zheng, Tianliang (Onco Targets Ther, 2018)
BACKGROUND: Autophagy plays a key role in the development of non-small-cell lung cancer (NSCLC). Beclin-1 is essential for the initiation and regulation of autophagy. Accumulated studies have investigated the prognostic role of Beclin-1 in NSCLC, but conclusions remain controversial. Therefore, we conducted this meta-analysis to assess the potential significance of Beclin-1 in NSCLC. MATERIALS AND METHODS: PubMed and Embase databases were searched for eligible studies published before December 31, 2017. Odds ratio (OR) was pooled to evaluate the clinicopathological significance of Beclin-1 in NSCLC. Hazard ratio (HR) was adopted to assess the association of Beclin-1 with overall survival (OS). RESULTS: Eight studies involving 1,159 patients were included in this meta-analysis. The pooled results showed that high Beclin-1 expression was significantly correlated with earlier tumor grade (OR=0.54, 95% CI: 0.36–0.81, P=0.003), less nodal involvement (OR=0.56, 95% CI: 0.37–0.86, P=0.007), earlier TNM stage (OR=0.62, 95% CI: 0.43–0.89, P=0.010), smaller tumor size (OR=0.54, 95% CI: 0.36–0.81, P=0.003), better differentiation (OR=0.48, 95% CI: 0.36–0.64, P<0.001), and less recurrence (OR=0.24, 95% CI: 0.14–0.41, P<0.001). Moreover, high level of Beclin-1 was significantly associated with better OS in NSCLC (HR=0.41, 95% CI: 0.26–0.64, P<0.001). CONCLUSION: Our meta-analysis suggests that high Beclin-1 expression predicts a better clinicopathological status and a better prognosis in NSCLC. Beclin-1 might act as a promising prognostic biomarker for NSCLC.